Kajian pemanfaatan limbah organik cair untuk pembiakan masal agens antagonis pseudomonas flourescens serta uji potensinya sebagai bio-pestisida - . Giyanto; Efi Toding Tondok (Jurnal Ilmu Pertanian Indonesia, 2009)
Pseudomonas fluorescens has been well known as biological control agent for plant diseases control. The ;:>roblem to apply the agents widely in the field or in the level of farmer is limited technology of mass production Nith low cost, due to the simple technology of propagation has not been yet available. The objective of this research is to study the potency of liquid organic wastes as media for mass production of P. f/uorescens and to formulate them as bio-pesticide. The results showed that modification of coconut water to pH of 7.0 could be used as media for growing P. flourescens. The P. fluorescens also could grow well in livestock liquid waste by adding 10% meat extract. On the other hand, the liquid tofu waste and liquid compost waste became good media for growing of P. fluorescens by addition of 10°/o meat extract and 1.2S0/o sugar. Tetes tebu will be very good media for P. f/uorescens at S% final concentration and by adding of 10°/o meat extract and 2.S0/o of sugar. The P. fluorescens showed high antagonistic effect to Ralstonia solanacearum and Sclerotium rolfsii in all of modified liquid organic wastes media. Survival and antagonisctic activity of P. fluorescens in modified organic liquid wastes stored at S°C or room temperature were 12 weeks. In vivo antagonistic and plant growth promoting activity showed that P. fluorescens grown in liquid organic waste suppressed the incidence of stem rot diseases caused by Sclerotium rolfsii and increased the vigor of plant growth on watermelon. Formulation of the P. Fluorescens grown in modified coconut water gave the best performance of P. fluorescens in supppressing of plant diseases and inducing plant growth. The product of BeMOR(e) (beneficial microorganism) from the result of this research will be proposed to be patented.